Grünau (Karakul Circulations: Colonial Economies and the Un_Making of Disciplinary Knowledges in Germany and Namibia, 2021)
156 JPEG files documenting participant observation in Grünau area
Keywords: History; Karakul sheep; COVID-19 (Disease); Postcolonialism; South Africa; Agriculture; Colonisation; Namibia; Swakara; Karakul Circulations; Colonial Economies; Karakul Farming; Germany; Colonial South-West Africa; German Colonialism; COVID-19; COVID-19 Pandemic; Karakul Sheep Industry